Molecular Targeting and Signal Transduction - Kumar, Rakesh (Cancer Treatment and Research, 2004)
Our limited understanding of cellular regulatory signal-transduction-networks has been a barrier to progress in improving the overall cure-rate of human cancers. Delineation of the physiologic roles of the specific regulatory signaling components, with known association with metastatic phenotypes, is a highly promising area which will likely provide the next generation of targeted strategies in the future of molecular cancer medicine. These signaling components are likely to be used in diagnosis, prognosis, and as novel targets for therapeutic development. This book brings together up-to-date summaries by leading cancer researchers on the major principles of cancer cell biology: survival, apoptosis, adhesion, and cell cycle deregulation. It is directed at clinicians and scientists working in the areas of experimental and molecular therapeutics, molecular medicine, translational cancer research, and bio-medical sciences in general